TITANIUM INCORPORATION AND VITI3+-IVTI4+ CHARGE TRANSFER IN SYNTHETIC DIOPSIDE - Skogby H.; Hålenius U.; Kristiansson P.; Ohashi H. (My University, 2006)
A series of Ti-doped diopside samples synthesized by fluxgrowth methods under reducing conditions were investigated by microanalytical methods and optical absorption spectroscopy, to assess Ti incorporation mechanisms, valence states, and related electronic transitions. Chemical characterization show that Ti occurs both in the tri-and tetravalent states, with Ti4+ preferentially ordered to the tetrahedral position whereas Ti3+ is restricted to the M1 position. Charge-balance is maintained by incorporation of Na and minor B, stemming from the flux compound. Polarized optical absorption spectra reveal three major absorption features. Two relatively narrow bands centered at 18 500 and 15 700 cm-1, mainly polarized in the crystallographic c-direction, display absorbance values that correlate with the calculated Ti3+ (M1) concentration, and are assigned to spin-allowed d-d transitions in Ti3+. A broader band centered around 24 500 cm-1 displays absorbance values that are well correlated with the product of VITi3+ and IVTi4+. Based on the spectral characteristics of this band, including a strong polarization in the crystallographic b-direction, we assign this band to an MITi3+-TTi4+ intervalence charge transfer process.
Keywords: CRYSTAL SYNTHESIS; DIOPSIDE; MAJOR AND MINOR ELEMENTS; OPTICAL SPECTROSCOPY; ORDER-DISORDER; PYROXENE; TI IN PYROXENE